Green synthesis of calcium silicate bioceramic powders. Issue 4 (May 2015) - Chen, Chun-Cheng; Ho, Chia-Che; Lin, Shao-Yung; Ding, Shinn-Jyh
Abstract: Calcium silicates have proven to be potential candidates for biomedical applications because of their osteogenic properties. Sol–gel methods are typically used for the preparation of calcium silicate powders. However, in the sol–gel route, an acid or base and ethanol are used to catalyze the precursors. From the perspective of green chemistry, it is better to avoid the use of organic solvents. The objective of this study was to prepare calcium silicate powders using a green synthesis route (hydrothermal method) without organic solvents. The powders were also prepared via the sol–gel process using tetraethoxysilane (TEOS) and calcium nitrate as the raw materials for the purpose of comparison. The powders were sintered at temperatures ranging from 600 to 1000 °C after the application of both methods. To understand the feasibility of using the resulting materials in medical applications for bone repair, the powders were mixed with water to form cements. The results indicated that the powder composition was not significantly affected by the different techniques but was dependent on the Ca:Si ratio of the precursors and on the sintering temperature. The different techniques produced no differences in powder morphology. In addition, the setting times of the powder-derived cements were found to be independent of the sintering temperature and synthesis technique, but it was affected by the Ca:Si ratio of the precursors. The mechanical strength of the cements was similar. These encouraging results suggest that the hydrothermal method is a potentially beneficial alternative to the sol–gel route for the production of calcium silicate powders.